Occurrence of antibodies to Toxoplasma gondii in rheas (Rhea americana) and ostriches (Struthio camelus) from farms of different Brazilian regions - Almeida,Amanda Brentano (2013)
This study aimed to verify the occurrence of antibodies againstToxoplasma gondii in rheas (Rhea americana) and ostriches (Struthio camelus) commercially breeding in Brazil. Blood samples from 20 rheas and 46 ostriches (young and adults) were serologically tested using a technique known as modified agglutination test (MAT) at an initial titration of 1:16 for ostriches and 1:25 for rheas. Antibodies against T. gondii were found in 50% (10/20) of the rheas, with titers ranging from 1:25 to 1:6,400. The incidence of antibodies against T. gondii in ostriches was 17.4% (8/46) with titers ranging from 1:16 to 1:256. Birds showing titers higher than 1:200 forT. gondii were mainly the young ones. Therefore, rheas and ostriches may be parasitized by T. gondii, showing high levels of antibodies against this parasite.